Nilai Tukar Petani dan Pola Pengeluaran Pangan pada Rumah Tangga Petani Padi di Desa Ramban Wetan - Nadila, Sinta Putri; Puryantoro, Puryantoro; Mayangsari, Andina (Universitas Galuh, 2025)
Farmers' Terms of Trade (NTP) and food expenditure share are critical indicators in measuring the economic welfare of farming households. NTP depicts farmers' purchasing power through the comparison of received (It) and paid (Ib) prices, while food expenditure share measures the proportion of income allocated to food and non-food needs. This study aims to analyze Farmers' Terms of Trade (NTP) and food expenditure share among rice farming households in Ramban Wetan Village, Cermee Subdistrict, Bondowoso Regency. The research employed a quantitative method using descriptive-analytic approach. A sample of 86 farmers was selected using stratified random sampling method. Research findings revealed that rice NTP was in a deficit condition at 83.84%, indicating low farmer welfare. The study of household expenditure share showed 64.98% was allocated to non-food needs, with an average of IDR 3,293,799 per planting season, categorizing these households as